An efficient secure communication for healthcare system using wearable devices. (October 2017) - Vijayakumar, P.; Pandiaraja, P.; Karuppiah, Marimuthu; Jegatha Deborah, L.
Highlights: An efficient multicast SMS alert system has been proposed to help the heart patients. An attack resistant end-to-end secure SMS alert system is ensured from patient to the doctor, relative, ambulance and hospital. This work is a novel approach for the remote health monitoring system for a heart patient. Abstract: In the present healthcare scenario, mobile phones play a vital role in performing secure text communications between different entities such as doctors, patients, hospitals, ambulances and other healthcare systems. Therefore, an efficient alert system for sending the private and confidential SMS messages has been proposed in this research work to send SMS alerts to healthcare entities from a heart patient. Very few research works have been proposed for multicast communication in SMS and each research work exposes some drawbacks as well. Since the proposed approach needs only one mod operation, the computational overhead of the proposed protocol is very low. Thus, the main advantage of this proposed work is that the messages are sent in a computationally efficient way and the experimental results confirm that the proposed work ensures end-to-end security with lower computational and communication overheads than the recent works in the literature. Graphical abstract: